Luck, Effort, and Reward in an Organizational Hierarchy - Audas, Rick; Barmby, Tim; Treble, John (Journal of Labor Economics, 2004)
Using the personnel records of a large British financial sector employer we investigate how workers respond to remuneration differences and “luck” in the promotion system. The results confirm that workers respond to larger remuneration spreads by working harder. Increased certainty in the promotion process also has this effect. There appears to be no difference between men’s and women’s reactions to promotion incentives. Gender differences in the raw data therefore appear not due to incentives. We need to look elsewhere for an explanation.